Desain Karakter Webtoon Tokoh Penemu Sains dan Teknologi untuk Remaja Usia 15-18 Tahun - Febriyanti Putri Ruspandi; Aris Sutejo; Sri Wulandari (Lembaga Pengembangan Kinerja Dosen, 2026)
The results of the 2022 PISA indicate that science skills and interest in Indonesia are still low. One way to increase interest in science is by introducing inventor figure of science and techonology. However, alternative learning media that are communicative and relevant to adolescents' media consumption habits are needed. Therefore, this study aims to design a character design for an inventor in the field of science and technology for a Webtoon comic as an educational tool for adolescents aged 15–18. This study used qualitative and quantitative methods. The qualitative method was used to understand the needs and interests of the target audience and to gather information from the literature for scientific sources in designing the inventor character. The quantitative method was used as one of the character design evaluation criteria, based on voting results by adolescents aged 15–18. The character design used Marika Nieminen's principles: demographics, silhouette and shape, color, and characteristics. Several alternatives were used to generate character designs, which were then evaluated to determine the final design. The character design evaluation will be assessed using several variables within an evaluation framework.